Sociological Study of the Impact of Intra-Group Social Capital on Political Culture (Case Study: Political Elites of Khuzestan Province) - Alihasan Fardbaboli; Abdoreza Hashemi; Ahmadali Hesabi (توسعه اجتماعی, 2022)
Elite political culture plays an important role in political development or underdevelopment, as can be acknowledged; the development of political culture is a necessary condition for political development, and the political development of societies is always measured by political culture. On the other hand; Attitudes and worldviews of elite political culture, if democratic, will lead to economic and social development, In the meantime, factors are influential in determining this type of political culture, the most important of which is social capital within the group. This article examines the relationship between intra-group social capital and political culture in a quantitative and survey manner. The sampling method was simple random sampling method and 214 political elites of Khuzestan province were selected as the sample. To assess political culture, Tessler standard questionnaire and researcher-made social capital questionnaire within the group were used. The results showed that the amount of social capital within the group was somewhat high (18.44) but the average political culture was moderate (19.154). The results also showed that there is a positive and significant relationship between the dimensions of social capital (trust, cohesion and intra-group participation) with political culture. And more than 19% of the variance of the political culture variable was explained by the two variables of intra-group trust and intra-group participation. In general, it can be said that social capital within a group can cause changes in the political culture of society.